Cosplay Collaboration Videos: Community Interactivity in Times of Pandemic - Edmund Hoff (Journal of Anime and Manga Studies, 2024)
Cosplay has developed with the influences of contemporary society since its early beginnings. From analog event-based interactions to online activities, this growth in popularity has been gradual and encountered challenges along the way. The COVID pandemic lockdown conditions of 2020, however, have been extremely disruptive for conventions. Cosplay activities online have changed from a supporting element of the physical event to being the only option available for a period. In tumultuous times human society has proved capable of adapting rapidly and popular culture is no different. Particularly during the early days of the restrictive measures, there was a burst of online activity and for the global cosplay community this manifested as cosplay collaboration videos. These cosplay community-based projects coalesced around themes familiar to the fandom from anime and manga to games and beyond. The global reach of the digital realm facilitated groups to come together in cooperation in a unique way which inspires further development of tools available to cosplayers.